The 75 greatest management decisions ever made-- and 21 of the worst - Crainer, Stuart (AMACOM Books, 1999)
Annotation "The 75 Greatest Management Decisions Ever Made is a pithy compendium that celebrates pinnacles of decision-making that have shaped management through the ages - and left their indelible impressions on business and society." "The 75 Greatest Management Decisions Ever Made represents managerial genius across all - not just business-related - spectrums. Exuberantly and undeniably fun, yet never frivolous or trivial, this book is a perceptive, instructive work that addresses serious issues in management and business strategy. Each entry describes a feat of management brilliance, extracts the invaluable lessons it contains, and explores its ultimate impact."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved